Letter from James Curtis Booth to Mr. Clark Caldwell - Booth, James Curtis (1881)
James Curtis Booth (1810-1888) informs a Mr. Clark Caldwell that he has decided against seeking a patent for a furnace part.
Keywords: Booth, James Curtis, 1810-1888; Patents; Furnaces